Peningkatan Kemampuan Mendeskripsikan Sifat–sifat Magnet dengan Pendekatan Scientific Siswa Kelas V SDN Balowerti I Kota Kediri Tahun Pelajaran 2015 / 2016 - Sumariati, Endang (Universitas Nusantara PGRI Kediri, 2018)
Student learning outcomes on learning to describe magnetic properties show that 51% of students score below the KKM. From the results that the author conducted a classroom action research. This study aims to improve KBM and improve student learning outcomes by using a scientific approach. The target of this learning improvement is the students of grade V SDN Balowerti I Kediri, amounting to 37 students. Data obtained through observation during KBM process and test to measure student learning outcomes. During cycle I and II has been an increase both student activeness and student learning outcomes. The average of student learning outcomes after initial learning was 66.47; 51% unfinished; 49% complete. Result of cycle I average value to be 76,35; 24% unfinished; 76% complete. While the results of cycle II average value increased to 82.03; 11% unfinished; and 89% complete. So with a scientific approach in learning to describe the properties of magnetism can help improve the activity and learning outcomes of students and can help improve how to teach teachers during the implementation of KBM in SDN Balowerti I Kediri.